(untitled) (Journal of Parents and Teachers, 2013)
In this frame social transformation that is accelerated , we have as expression Maximum crisis economic in which we are immersed , a proposal arises exchange is encouraging the mentality entrepreneurial of citizens and an alternative promising face-to address Current situation systemic unemployment.